The Role of Employee Engagement Mediating Digital Leadership and Organizational Support on Employee Performance at Siloam Bali Hospital - MARIANI, Kadek Lina; SANTOSO, R Tri Priyono Budi; KOMALASARI, Yeyen; JUNAEDI, I Wayan Ruspendi (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:The research on this occasion aimed to determine the influence of digital leadership and organizational support on employee performance, mediated by employee involvement among Siloam Hospital Bali employees. Methodology :The method used in carrying out this research is a quantitative approach. The sample that supports this research is employees recorded as working at Siloam Hospital Bali with a total of 84 data. The techniques used to make searching and collecting data easier are questionnaires, interviews and documentation accompanied by observation. The analytical technique used to answer the hypothesis is quantitative descriptive analysis and Partial Least Square (PLS) applying the Structural Equation Modeling (SEM) equation model. Findings :The results of this series of research show that 1) digital leadership without providing results influences employee engagement, 2) digital leadership without providing results influences employee performance, 3) organizational support provides results with a positive influence and occurs significantly on employee engagement, 4) organizational support provides results with a positive influence and significant attitude on employee performance. Implication :5) employee engagement provides results with a positive influence and significant relationship on employee performance, 6) employee engagement without being able to mediate the influence of digital leadership on employee performance, 7) engagement employees succeeded in mediating the influence of organizational support on employee performance.